Kontribusi al-Ramāhurmuzi Terhadap Perkembangan Ilmu Hadis: Analisis Terhadap Kitab al-Muhaddits al-Fāshil Baina al-Rāwi wa al-Wā’i - Irwan Abdurrohman; Rizal Samsul Mutaqin (Diroyah : Jurnal Studi Ilmu Hadis, 2021)
The science of hadith has changed along with the times, starting from the prophet's era. The fourth century is considered a golden age for the development of hadith science. It became a scientific discipline that separated from other knowledge with the creation of the book by al-Ramahurmuzi. Using the literature study method and the content analysis approach, in the book Al-Muhaddits al-Fāshil Baina al-Rawi Wa al-Wa'i, Al-Ramahurmuzi made it a significant contribution to the development of the science of hadith because he became the first basis. With the birth of the book, the development the hadith science became the basis delivery of books by other scholars of hadith science so that its benefits can continue until now. Specifically in the science of ruwat and the history of hadith, Al-Ramahurmuzi provides a long explanation and quotes related narrations